2021
DOI: 10.3390/jpm11111167
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality-Based Therapy Reduces the Disabling Impact of Fibromyalgia Syndrome in Women: Systematic Review with Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Virtual reality-based therapy (VRBT) is a novel therapeutic approach to be used in women with fibromyalgia syndrome (FMS). The aim of our study is to assess the effect of VRBT to reduce the impact of FMS in outcomes such as pain, dynamic balance, aerobic capacity, fatigue, quality of life (QoL), anxiety and depression. Methods: Systematic review with meta-analysis was conducted from a bibliographic search in PubMed, Scopus, PEDro, Web of Science and CINAHL until April 2021 in accordance with PRISMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 97 publications
(243 reference statements)
0
11
0
Order By: Relevance
“…DIHIs can actuate in different neuroanatomic areas related to pain perception (known as the “pain matrix”), such as the anterior cingulate cortex, the insula, the thalamus, and the primary and secondary somatosensory cortexes [ 82 , 83 ]. The distraction power of DIHIs affects the neurophysiological networks between the visual and somatosensory systems, diverting attention and leading to a slower response to incoming pain signals [ 25 , 84 ]. Interacting with DIHIs can favor the proliferation of positive emotions that produce endogenous pain reduction and a feeling of well-being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DIHIs can actuate in different neuroanatomic areas related to pain perception (known as the “pain matrix”), such as the anterior cingulate cortex, the insula, the thalamus, and the primary and secondary somatosensory cortexes [ 82 , 83 ]. The distraction power of DIHIs affects the neurophysiological networks between the visual and somatosensory systems, diverting attention and leading to a slower response to incoming pain signals [ 25 , 84 ]. Interacting with DIHIs can favor the proliferation of positive emotions that produce endogenous pain reduction and a feeling of well-being.…”
Section: Discussionmentioning
confidence: 99%
“…The latest technological advances have allowed the development of digital and interactive health interventions (DIHIs) for women with BC. The use of virtual reality (VR) devices and smartphone apps has allowed the development of videogame-based interventions that reduce the impact of different pathologies [ 25 , 26 ], including BC [ 27 ], through the practice of various physical and cognitive exercises. On the one hand, virtual-reality-based therapy (VRBT) allows patients to interact with and immerse themselves in a computer-generated environment that can make them feel as if they are actually present in that world, offering immersive, semi-immersive, and non-immersive experiences depending on the type of VR.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality technology that allows individuals to be included in a virtual environment similar to the real world through a computer and interact with it has shown promising results in managing pain, anxiety or mood states and reducing the impact of fibromyalgia in women ( Cortés-Pérez et al, 2021 ). An app has also been developed to promote self-care as a mobile health resource complementary to physiotherapy in fibromyalgia management.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The accepted topics included a variety of research studies, from study protocols [ 6 ] to original qualitative [ 7 , 8 , 9 ] and quantitative studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Additionally, review protocols [ 18 , 19 ] and literature reviews [ 20 , 21 , 22 , 23 ] were included, covering different areas of care, from studies addressing ageism [ 6 ] or stigma [ 17 ] to a personalized approach to diagnosing and managing ischemic stroke [ 16 ]. We highlighted the importance of recognizing that in order to enhance healthcare delivery, all stakeholders involved in providing care must actively partner with patients and families to enable changes in the care process, obtaining higher patient satisfaction and better health outcomes.…”
mentioning
confidence: 99%
“…Second, we highlight a study aiming to assess the effect of virtual-reality-based therapy to reduce the impact of fibromyalgia syndrome in outcomes such as pain, dynamic balance, aerobic capacity, fatigue, quality of life, anxiety, and depression. The findings demonstrated that virtual-reality-based therapy can effectively reduce pain, fatigue, anxiety, and depression and increase dynamic balance, aerobic capacity, and quality of life in women with fibromyalgia syndrome [ 21 ].…”
mentioning
confidence: 99%